Fundamentals of veterinary clinical pathology - Stockham, Steven L.; Scott, Michael Alan (USA : Blackwell Publishing, 2008)
This book provides in-depth information about common clinical laboratory assays that are used to evaluate domestic mammals, including what assays measure, sample or assy conditions that affect results, and what results indicate about the physiologic or pathologic state of a patient. Whenever possible, diseases and conditions are grouped by common mechanisms or processes to promete a conceptual understanding of laboratory data that can be generally applied across many species.
Keywords: PATOLOGIA VETERINARIA; LABORATORIOS VETERINARIOS; Análisis clínicos- -- Prácticas de laboratorio; DIAGNOSTICO DE LABORATORIO VETERINARIO